PENGARUH TERAPI BERMAIN JENGA TERHADAP PENURUNAN KECEMASAN PADA ANAK USIA PRASEKOLAH (4-6 TAHUN) AKIBAT HOSPITALISASI DI MURNI TEGUH MEMORIAL HOSPITAL - Tamara, Livia; Daniel Hasibuan, Muhammad Taufik (Universitas Murni Teguh, 2023)
Hospitalization is a process that plans or emergency requires the child to stay in the hospital, to undergo therapy and treatment until his return home. Hospitalization has a psychological impact in several ways, such as depression, stress, fear and experiencing anxiety. One of the recommended interventions is the provision of jenga play therapy. The purpose of this study aims to find out the effect of jenga play therapy on decreasing anxiety in preschool-aged children (4-6 years) due to hospitalization at Murni Teguh Memorial Hospital. This type of research is quasy experimental with the design